2008
DOI: 10.1029/2007ja012975
|View full text |Cite
|
Sign up to set email alerts
|

Survey of magnetosonic waves and proton ring distributions in the Earth's inner magnetosphere

Abstract: [1] Fast magnetosonic waves can lead to the local acceleration of electrons from $10 keV up to a few MeV on a timescale of 1-2 d and may play an important role in radiation belt dynamics. Here we present a survey of wave and particle data from the Combined Release and Radiation Effects Satellite (CRRES) to determine the global morphology of the waves as a function of magnetic activity, and to investigate the role of proton rings as a potential source mechanism. The intensity of fast magnetosonic waves in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
267
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(288 citation statements)
references
References 65 publications
20
267
1
Order By: Relevance
“…/T k is reduced to unity for each component, showing that the instability is not driven by the temperature anisotropy, but by the ring-like distribution. Note that equatorial magnetosonic waves [Meredith et al, 2008] at harmonics of W cp are also thought to be driven by a ring-like distribution function. But those waves are predominantly compressional (C B = (dB k ) 2 /(dB) 2 close to unity).…”
Section: Analysis Of Instabilitymentioning
confidence: 99%
“…/T k is reduced to unity for each component, showing that the instability is not driven by the temperature anisotropy, but by the ring-like distribution. Note that equatorial magnetosonic waves [Meredith et al, 2008] at harmonics of W cp are also thought to be driven by a ring-like distribution function. But those waves are predominantly compressional (C B = (dB k ) 2 /(dB) 2 close to unity).…”
Section: Analysis Of Instabilitymentioning
confidence: 99%
“…Interaction between plasmaspheric hiss and energetic electrons is a major loss process inside the plasmapause for electron energies from 0.1 to a few MeV (Lyons and Thorne, 1973;Meredith et al, 2007Meredith et al, , 2009. Magnetosonic waves may also be an important acceleration mechanism Meredith et al, 2008Meredith et al, , 2009Mourenas et al, 2013) and EMIC waves may be an important loss mechanism for MeV electrons Meredith et al, 2003;Jordanova et al, 2008). However, the roles of magnetosonic and EMIC waves in relativistic electron dynamics has yet to be fully assessed, and are not considered further here.…”
Section: A Sicard-piet Et Al: Effect Of Plasma Density On Diffusionmentioning
confidence: 99%
“…Both observations [Meredith et al, 2008] and simulations [Chen et al, 2010;Liu et al, 2011;Ma et al, 2014] have shown that such equatorial MS waves are preferentially excited by proton ring distributions. The signatures of MS waves include their low ellipticity, which leads to nearly linear polarization, and their nearly perpendicular propagation, which results in much stronger E ⟂ and B ∥ components compared to E ∥ and B ⟂ components, respectively .…”
Section: Introductionmentioning
confidence: 99%